An atypical presentation of herpes simplex virus infection in Harlequin ichthyosis. Issue 6 (31st August 2018) - Yang, Shelley; Bayart, Cheryl; Brandling‐Bennett, Heather
Abstract: We present an atypical presentation of herpes simplex virus infection in a patient with Harlequin ichthyosis, which we attribute to abnormal cornification.